2015
DOI: 10.1371/journal.pone.0131409
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Prognosis of Metaplastic Breast Carcinoma: Experience of a Major Chinese Cancer Center

Abstract: Metaplastic breast carcinoma (MBC) is a rare heterogeneous group of primary breast malignancies, with low hormone receptor expression and poor outcomes. To date, no prognostic markers for this tumor have been validated. The current study was undertaken to evaluate the clinicopathologic characteristics, the response to various therapeutic regimens and the prognosis of MBCs in a large cohort of patients from Tianjin Medical University Cancer Hospital in China. Ninety cases of MBCs diagnosed in our hospital betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
71
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 27 publications
9
71
2
2
Order By: Relevance
“…There was inconsistency in data handling and analysis. While some authors performed matching (4,813,15), some did not match instead they compared with either all TNBC (14) or with BC regardless of tumor molecular subtype (5). There was also inconsistency in the chosen variables for matching, ranging from only one variable such as Nottingham grade (4), or stage (12), to a more comprehensive matching including age, stage, and therapy modality (11 and current study).…”
Section: Discussionmentioning
confidence: 99%
“…There was inconsistency in data handling and analysis. While some authors performed matching (4,813,15), some did not match instead they compared with either all TNBC (14) or with BC regardless of tumor molecular subtype (5). There was also inconsistency in the chosen variables for matching, ranging from only one variable such as Nottingham grade (4), or stage (12), to a more comprehensive matching including age, stage, and therapy modality (11 and current study).…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic activity is usually moderate to high and areas of necrosis may be present. 17 In a major Chinese cancer centre study by yiqian Zhang et al 18 they got spindle cell carcinoma as the most common variant, G M Tse et al 19 found in their study metaplastic carcinoma with sarcomatoid component was the most common type of MBC (70.58%) but in our study, (Table.IV), we got metaplastic squamous cell carcinoma as the most common type of MBC. we had small number of case study in 7 years period in our population group.…”
mentioning
confidence: 49%
“…Isso poderia explicar a menor taxa de sobrevida 10 . Esses tumores geralmente são receptores hormonais negativos e não respondem ao tratamento clínico 11 . Contudo, apesar do grande tamanho, têm pouco envolvimento linfonodal.…”
Section: Discussionunclassified
“…Um estudo com 90 pacientes mostrou menor acometimento dos linfonodos axilares (20,8%) em relação aos carcinomas não metaplásicos, ainda que esse acometimento seja maior em relação aos sarcomas mamários. Todavia, estes tumores possuem alta probabilidade de metástase, mesmo com pouco acometimento linfonodal 11 . O estudo imunoistoquímico é fundamental para o estabelecimento do diagnóstico.…”
Section: Discussionunclassified